Designing of dynamic polyethyleneimine (PEI) brushes on polyurethane (PU) ureteral stents to prevent infections. (15th July 2015) - Gultekinoglu, Merve; Tunc Sarisozen, Yeliz; Erdogdu, Ceren; Sagiroglu, Meral; Aksoy, Eda Ayse; Oh, Yoo Jin; Hinterdorfer, Peter; Ulubayram, Kezban
Graphical abstract: Abstract: Permanent antibacterial coatings have been developed by brush-like polyethyleneimine (PEI) on polyurethane (PU) ureteral stents since bacterial adhesion and biofilm formation with the following encrustation on stent surface limit their long term usage. In order to control or prevent bacterial infections; PEI chains with two different molecular weights (Mn: 1800 or 60, 000 Da) were covalently attached on the polyurethane (PU) surface by "grafting to" approach to obtain a brush-like structure. Then, PEI brushes were alkylated with bromohexane to enhance the disruption of bacterial membranes with increasing polycationic character. X-ray Photoelectron and Infrared Spectroscopy investigations confirmed that PEI grafting and alkylation steps were performed successfully. Surface roughness in dry state increased dramatically from 65.8 nm to 277.7 nm and 145.2 nm for short chain PEI and long chain PEI grafted samples, respectively. Both low and high molecular weight PEI grafts exhibited a brush-like structure and potent antibacterial activity by lowering the adherence of Klebsiella pneumonia, Escherichia coli and Proteus mirabilis species up to two orders of magnitude without any cytotoxic effect on L929 and G/G cells. Thus, permanent bactericidal activity was achieved by the contact-active strategy of dynamic PEI brush-like structures on polyurethane ureteral stent.